Occurrence and impacts of gastrointestinal symptoms in team-sport athletes: a preliminary survey - Wilson, P. B.; Fearn, R.; Pugh, J. (Clinical Journal of Sport Medicine, 2023)
Objectives: Although gastrointestinal (GI) symptoms are prevalent in endurance athletes, scant research has examined GI symptoms in team-sport athletes, their impacts, and explanatory factors. This study aimed to assess the prevalence and severity of GI symptoms in team-sport athletes and identify potential risk factors.